Marketing Communication Strategy of the Youth and Sports Tourism Office in Promoting Muaro Jambi Temple - Yuliandari*, Miski; Anom, Erman (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
This research is motivated by the importance of tourism promotion activities in an effort to increase the number of tourists in a tourist destination. The Muaro Jambi Regency Youth and Sports Tourism Office certainly has the right marketing communication strategy to attract visitors. This research aims to find out how the marketing communication strategy is carried out by the Muaro Jambi Regency Tourism, Youth and Sports Office. This research uses a descriptive qualitative research method with a case study approach, data sources were obtained through observation, documentation and interviews with informants from the Muaro Jambi Regency Youth and Sports Tourism Office, namely the Head of the Tourism Division, the Head of the Tourism Destination Section, and the Head of the Tourism Marketing Section. The data collection technique in this research uses observation or direct observation. The findings from this research are the marketing communication strategy activities carried out by the Tourism, Youth and Sports Department in promoting Muaro Jambi Temple by utilizing social media, mass media, print media such as newspapers, local television media, word of mouth promotions and through temple festivals held every year.